2007
DOI: 10.1021/es071359r
|View full text |Cite
|
Sign up to set email alerts
|

False Cyanide Formation during Drinking Water Sample Preservation and Storage

Abstract: Carefully controlled bench-scale and on-site experiments demonstrated that cyanide can form in the treated drinking water sample container during preservation and storage. In the bench-scale experiment, treated tap water samples were collected on 20 days over six months. The tap water samples were split and some of the splits were spiked with formaldehyde, a known ozone disinfection byproduct, held for three hours and tested for cyanide. Then they were preserved and held for 2-10 days. None of the 69 initial s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…“Follow the method.” For regulatory drinking water testing, laboratories are required to “follow the method,” including procedures for how samples are preserved and treated for potential interferences. This regulatory mantra is problematic for cyanide (Delaney & Blodget 2016a), and similar false positives from the sample preservation and testing have been demonstrated (Delaney et al 2007). Cyanide formation during wastewater preservation and testing has also been demonstrated (Stanley & Antonio 2012, Khoury et al 2008, Carr et al 1997, Delaney et al 1997).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…“Follow the method.” For regulatory drinking water testing, laboratories are required to “follow the method,” including procedures for how samples are preserved and treated for potential interferences. This regulatory mantra is problematic for cyanide (Delaney & Blodget 2016a), and similar false positives from the sample preservation and testing have been demonstrated (Delaney et al 2007). Cyanide formation during wastewater preservation and testing has also been demonstrated (Stanley & Antonio 2012, Khoury et al 2008, Carr et al 1997, Delaney et al 1997).…”
Section: Discussionmentioning
confidence: 96%
“…Cyanide has an additional level of complexity in that it can be formed or destroyed by a variety of chemical reactions (ASTM 2009). Previous studies demonstrated that cyanide can form in the preserved sample container (Delaney et al 2007), or during the sample preservation and analysis (Delaney & Blodget 2016a). This simple but illuminating experiment using deionized water in place of a raw drinking water supply was conducted to verify previous observations regarding FCN formation during drinking water treatment and cyanide testing.…”
mentioning
confidence: 99%
“…Protocols used for sample collection through analysis can sometimes result in serious errors and misclassification of results. Compounds attributed to reaction of natural organic matter (NOM) with both FAC and ozone have been misidentified as novel DBPs due to analytical artifacts (Campbell et al, 1987; Delaney et al, 2007; Dietrich et al, 1988; Kristiansen et al, 1994; Wang et al, 1988; Xie & Reckhow, 1993; Xie & Reckhow, 1994; Xie & Reckhow, 1997). In some cases, artifacts resulted from interactions between organic solvents used during solvent extraction or derivatization in the presence of FAC, bromine, or ozone.…”
Section: Introductionmentioning
confidence: 99%
“…For the manual and automated pyridine–barbituric acid–chloramine‐T colorimetric cyanide methods, interferences are reported to include aldehydes, carbonates, fatty acids, nitrate, nitrite, oxidants, sugars, sulfide, other sulfur compounds, thiocyanate, and turbidity (ASTM Method 7365‐09a, ASTM, 2009). For example, even in drinking water we demonstrated false cyanide can be formed in the sample container after proscribed sample preservation (Delaney, 2007). This has led us to distill our quarterly drinking water total cyanide samples on‐site at the time of sampling at the drinking water treatment plant to avoid forming false cyanide in the container due to the preservation treatment.…”
Section: Introductionmentioning
confidence: 99%